Greece : Third Review Under the Stand-By Arrangement-Staff Report; Informational Annex; Press Release on the Executive Board Discussion; Statement by the Staff Representative on Greece; and Statement by the Executive Director for Greece. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, Greece's economic program has progress toward its sustainable growth by boosting competitiveness, strengthening financial sector stability, and securing sustainable public finances. The fiscal and broader reforms are to achieve the program's medium-term objectives. Structural reforms are being deepened to support recovery. More sufficient use of state assets will support fiscal adjustment efforts, promote growth and employment, and help Greece retire maturing debt. The financial system remains stable, and time is needed to allow banks to deleverage and restructure in an orderly fashion.